2013
DOI: 10.1016/j.metabol.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Branched chain amino acids are novel biomarkers for discrimination of metabolic wellness

Abstract: Objective To identify novel biomarkers through metabolomic profiles that distinguish metabolically well (MW) from metabolically unwell (MUW) individuals, independent of body mass index (BMI). Materials/Methods This study was conducted as part of the Measurement to Understand the Reclassification of Disease of Cabarrus/Kannapolis (MURDOCK) project. Individuals from 3 cohorts were classified as lean (BMI<25 kg/m2), overweight (BMI≥25 kg/m2, BMI<30 kg/m2) or obese (BMI≥30 kg/m2). Cardiometabolic abnormalities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
160
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 200 publications
(180 citation statements)
references
References 23 publications
11
160
1
8
Order By: Relevance
“…PCA showed that altered plasma levels of AA and some of their metabolites, such as kynurenine (Kyn) and C5 acylcarnitine, are associated with many adiposity markers, as reported by other groups (3,24,33,42,44). One other study had examined associations between levels of glutamine, leucine, isoleucine, phenylalanine, and tyrosine and visceral obesity (25).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…PCA showed that altered plasma levels of AA and some of their metabolites, such as kynurenine (Kyn) and C5 acylcarnitine, are associated with many adiposity markers, as reported by other groups (3,24,33,42,44). One other study had examined associations between levels of glutamine, leucine, isoleucine, phenylalanine, and tyrosine and visceral obesity (25).…”
Section: Discussionmentioning
confidence: 83%
“…Significantly higher plasma BCAA, aromatic amino acids (AAA), and C3 and C5 acylcarnitine levels are also found among metabolically unwell versus metabolically well individuals, independent of BMI (3). Results regarding alterations in other AA remain inconsistent (3,18,33).…”
mentioning
confidence: 99%
“…Tai et al have shown that increased levels of some AAs such as alanine, proline, and valine were correlated with insulin resistance in Asian men (52). BCAAs could be considered as novel biomarkers for discrimination of metabolic wellness independent of body mass index (6). It has been asserted that higher concentrations of BCAAs in obesity cause or exacerbate insulin resistance through mechanisms involving activation of the mammalian target of rapamycin (mTOR) (40).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the BCAA catabolic pathway is enriched for carbonylation is intriguing because serum levels of BCAAs are positively associated with obesity and insulin resistance (63)(64)(65)(66)(67)(68). The BCAAs (leucine, isoleucine, and valine) are important sources of succinyl-CoA and acetylCoA to replenish the TCA cycle in adipocytes in order to fuel lipogenesis.…”
Section: Lipid Peroxidation and Apoptosismentioning
confidence: 99%